Effect of helical micro-fins on two-phase flow behavior of R410A evaporating in horizontal round tubes obtained through visualization. (December 2019) - Yang, Cheng-Min; Hrnjak, Pega
Highlights: 3D printed clear helical micro-fin tubes are made for visualization. Helical grooves enable the liquid to reach a higher location in tubes. Helix angle influences the transition from stratified flow to annular flow. Tubes with different groove directions help understand the flow behavior. Abstract: This paper presents a new approach in visualization of the evaporation mechanism and the two phase flow. The visualization test section is a transparent micro-fin tube made by 3D printing. The 3D printing technology helps reproduce the real geometry in commercial metal micro-fin tubes. Even though the wall material is different from the real metal, this new method provides a more complete understanding of the mechanisms of flow boiling and the heat transfer enhancement due to micro-fin geometry. To investigate the effect of micro-fin geometries on two-phase flow behavior, R410A flow boiling experiments are conducted at 10 °C saturation temperature and visualized through a clear smooth tube and micro-fin tubes of 0°, 10° and 18° helix angles. The results showed that the annular flow pattern in the helical micro-fin tube occurred at a lower vapor quality than the smooth and axial micro-fin tubes. Helix angle affects the transition boundary of stratified wavy flow to wavy annular flow, which shifts downward (to lower mass flux and vapor quality conditions) as the helix angle increases. Other transitions are not significantly affected by the helix angle. Helical micro-fin tubes with different groove directions were made to understand the flow behavior on the upward side and downward side of the tube.